Bi-Level ventilation decreases pulmonary shunt and modulates neuroinflammation in a cardiopulmonary resuscitation model - Ruemmler, Robert; Ziebart, Alexander; Kuropka, Frances; Duenges, Bastian; Kamuf, Jens; Garcia-Bardon, Andreas; Hartmann, Erik K. (PeerJ, 2020)
Background Optimal ventilation strategies during cardiopulmonary resuscitation are still heavily debated and poorly understood. So far, no convincing evidence could be presented in favour of outcome relevance and necessity of specific ventilation patterns. In recent years, alternative models to the guideline-based intermittent positive pressure ventilation (IPPV) have been proposed. In this randomized controlled trial, we evaluated a bi-level ventilation approach in a porcine model to assess possible physiological advantages for the pulmonary system as well as resulting changes in neuroinflammation compared to standard measures. Methods Sixteen male German landrace pigs were anesthetized and instrumented with arterial and venous catheters. Ventricular fibrillation was induced and the animals were left untreated and without ventilation for 4 minutes. After randomization, the animals were assigned to either the guideline-based group (IPPV, tidal volume 8–10 ml/kg, respiratory rate 10/min, FiO21.0) or the bi-level group (inspiratory pressure levels 15–17 cmH2O/5cmH2O, respiratory rate 10/min, FiO21.0). Mechanical chest compressions and interventional ventilation were initiated and after 5 minutes, blood samples, including ventilation/perfusion measurements via multiple inert gas elimination technique, were taken. After 8 minutes, advanced life support including adrenaline administration and defibrillations were started for up to 4 cycles. Animals achieving ROSC were monitored for 6 hours and lungs and brain tissue were harvested for further analyses. Results Five of the IPPV and four of the bi-level animals achieved ROSC. While there were no significant differences in gas exchange or hemodynamic values, bi-level treated animals showed less pulmonary shunt directly after ROSC and a tendency to lower inspiratory pressures during CPR. Additionally, cytokine expression of tumour necrosis factor alpha was significantly reduced in hippocampal tissue compared to IPPV animals. Conclusion Bi-level ventilation with a constant positive end expiratory pressure and pressure-controlled ventilation is not inferior in terms of oxygenation and decarboxylation when compared to guideline-based IPPV ventilation. Additionally, bi-level ventilation showed signs for a potentially ameliorated neurological outcome as well as less pulmonary shunt following experimental resuscitation. Given the restrictions of the animal model, these advantages should be further examined.
Keywords: Resuscitation; Ventilation; Pig; Bi-level; MIGET; Oxygenation; Gas Exchange; Neuroinflammation